Anonymous Versus Self-Identified Response Formats for School Mental Health Screening. (March 2022) - Wagle, Rhea; Dowdy, Erin; Furlong, Michael J.; Nylund-Gibson, Karen; Carter, Delwin; Hinton, Tameisha
Schools are an essential setting for mental health supports and services for students. To support student well-being, schools engage in universal mental health screening to identify students in need of support and to provide surveillance data for district-wide or state-wide policy changes. Mental health data have been collected via anonymous and self-identified response formats depending on the purpose of the screening (i.e., surveillance and screening, respectively). However, most surveys do not provide psychometric evidence for use in both types of response formats. The current study examined whether responses to the Social Emotional Health Survey–Secondary (SEHS-S), a school mental health survey, are comparable when administered using anonymous versus self-identified response formats. The study participants were from one high school and completed the SEHS-S using self-identified ( n = 1, 700) and anonymous ( n = 1, 667) formats. Full measurement invariance was found across the two response formats. Both substantial and minimal latent mean differences were detected. Implications for the use and interpretation of the SEHS-S for schoolwide mental health are discussed.